TOKSISITAS LIMBAH CAIR LATEKS TERHADAP KELANGSUNGAN HIDUP, PERTUMBUHAN DAN TINGKAT KONSUMSI OKSIGEN IKAN PATIN (Pangasius sp) - Ofan Bosman; Ferdinand Hukama Taqwa; Marsi . (Universitas Sriwijaya, 2013)
The purposes of this research are to determine the value of LC50 96 hours and sub lethal toxicity test of latex liquid waste against survival, growth and oxygen consumption rate of catfish. This research was held from April until June 2013 in Laboratory of Basic Fisheries, Faculty of Agriculture, Sriwijaya University. The materials used for this research were latex liquid waste and catfish was a length of 11 cm ± 0.1 cm with a weight of 10 g ± 1 g as bioassay. This research used a completely randomized design (CRD) with seven treatments and three replications. Treatment levels of lethal toxicity test were 0 mL.L-1 (A), 16.8 mL.L-1 (B), 18.8 mL.L-1 (C), 21.0 mL.L-1 (D), 23.5 mL.L-1 (E), 26.3 mL.L-1 (F) and 29.4 mL.L-1 (G). Treatment levels of sub lethal toxicity tests were 0% x LC50 96 hours (A), 0.5% x LC50 96 hours (B), 1% x LC50 96 hours (C), 6.25% x LC50 96 hours (D), 12.5% ​​x LC50 96 hours (E), 25% x LC50 96 hours (F) and 50% x LC50 96 hours (G). The result of this research showed that the of LC50 96 hours concentration of latex liquid waste for catfish is 24.5 mL.L-1. The results of sub lethal toxicity test indicated that latex liquid waste significantly affect the survival of catfish in the concentration of 25% x LC50 96 hours (F), while did not significantly affect on growth until concentration of 50% x LC50 96 hours (G). Exposure time periode affects oxygen consumption rate was concentration from 0,5% x LC50 96 hours (B) until 50% x LC50 96 hours (G) where the longer of exposure time would decrease the oxygen consumption of catfish. Keywords: Latex Liquid Waste, Toxicity, Catfish